Ayurvedic Management of Anorexia Nervosa (International Journal of Ayurveda and Pharma Research, 2025)
Anorexia nervosa (AN) is a complex eating disorder characterized by extreme food restriction, intense fear of gaining weight, and a distorted body image. One-year prevalence of anorexia nervosa is 0.16% for females and 0.09% for males. Ayurveda approaches to addressing both the physical and mental aspects of Anorexia Nervosa (AN). From an Ayurvedic perspective, AN can be interpreted as Kapha-Pittika Unmada, a mental imbalance caused by the aggravation of Kapha and Pitta doshas, which impacts both nutritional and psychological well-being. Methods: 17-year-old male patient, recently exhibited increased food intake followed by self-induced vomiting and has been hiding food and diagnosed with anorexia nervosa, referred to as Kapha-Pittika Unmada in Ayurveda. The treatment protocol was designed to target Kapha and Pitta imbalances while strengthening the Manovaha Srotas to support the patient’s physical and psychological recovery. Ayurvedic interventions included internal and external therapies aimed Shodhana, Shamana and Satvavajaya measures. Results: The patient demonstrated positive outcomes, including gradual weight gain, improved dietary habits, and a decrease in elimination behaviors. Psychological improvements were also noted, particularly in terms of reduced anxiety and improved mood and quality of life also improved. Discussion: The treatment protocol included Samana (pacifying therapies), Shodhana (cleansing therapies), Dhara (therapeutic pouring of medicated liquids), Thalam (application of medicated paste to the head), and Dhupanam (medicated fumigation) along with Satvavaja measures. Future studies should investigate the integration of Ayurvedic treatments with modern psychological therapies to establish comprehensive and sustainable treatment protocols for anorexia nervosa.